The Looming Cybersecurity Crisis and What It Means for the Practice of Industrial and Organizational Psychology. Issue 2 (19th June 2018) - Dreibelbis, Rachel C.; Martin, Jaclyn; Coovert, Michael D.; Dorsey, David W.
Abstract : The persistently changing landscape of cyberspace and cybersecurity has led to a call for organizations' increased attention toward securing information and systems. Rapid change in the cyber environment puts it on a scale unlike any other performance environment typically of interest to industrial and organizational (I-O) psychologists and related disciplines. In this article, we reflect on the idea of keeping pace with cyber, with a particular focus on the role of practicing I-O psychologists in assisting individuals, teams, and organizations. We focus on the unique roles of I-O psychologists in relation to the cyber realm and discuss the ways in which they can contribute to organizational cybersecurity efforts. As highlighted throughout this article, we assert that the mounting threats within cyberspace amount to a "looming crisis." Thus, we view assisting organizations and their employees with becoming resilient and adaptive to cyber threats as an imperative, and practicing I-O psychologists should be at the forefront of these efforts.